Factors Affecting the Implementation of Character Education Program Policies at SMAN 2 Sipora in Mentawai Islands Regency - Noralina Matondang; Desna Aromatica; Fatia Fatimah (International Journal of Educational Dynamics, 2022)
This study aims to analyze the factors that influence the implementation of character education program policies at Senior High School (SMAN) 2 Sipora in Mentawai Islands Regency, this is motivated by the weakness of the internal quality assurance system for character education. implementation as a need to ensure the quality of character education, deviant behavior among school-age teenagers, the lack of distribution of character education for students, and the lack distribution of character education to students by teachers at SMAN 2 Sipora. This type of research uses a quantitative approach with a multiple linear regression method. Data collection techniques with questionnaires. The respondents of this study were 56 teachers at SMAN 2 Sipora. The sampling method used the total sampling method where the entire population in this study was used as the research sample. Hypothesis testing is calculated with the IBM Statistical Package for Social Science (SPSS) version 24.0 program. From the results of this study, it was found that partial communication had no significant effect on the implementation of character education program policies, resources had a significant effect on the implementation of character education program policies, disposition had a significant effect on the implementation of character education program policies, the bureaucratic structure had a significant effect on the implementation of character education program policies at SMAN 2 Sipora. Simultaneously, communication, resources, disposition, and bureaucratic structure significantly influence the implementation of character education program policies at SMAN 2 Sipora.